Surviving M&A make the most of your company being acquired - Moeller, Scott (Wiley, 2009)
"Since Intelligent M&A was released in June 2007, the short and final chapter on How to survive a merger has received a lot of attention and the information provided therein appears to be robust enough to withstand that attention. Therefore, the proposed book will build on the organisation of that chapter and would be divided roughly into the following chapters: - Background on mergers and acquisitions: why companies merge and what happens to employees in those mergers - The first decision facing employees: stay or leave? - Attitude and personal performance - Timing issues: when to act? - Preparation during the pre-merger phase - Should you rely on your boss (and to what degree to 'trust' the company)? - The need to stay around the office - Taking care of your own team - Networking internally and externally - Maintaining clients - The importance of flexibility in accepting new assignments - Preparing for the worst Written in an engaging style, with real global case studies, this is an extremely valuable guide for any manager or employee concerned about their jobs when their companies are undergoing a corporate restructuring. (NB. The book is intended to be of use to readers globally. It therefore does not have a chapter on legal issues in being made redundant, as this information is out-dated quickly, isn't the expertise of the author and is available from experts elsewhere)"--Provided by publisher.